2017
DOI: 10.1002/ange.201706781
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Decarboxylative Alkynylation of N‐Hydroxyphthalimide Esters with Bromoalkynes

Abstract: An ew method for the synthesis of terminal and internal alkynes from the nickel-catalyzed decarboxylative coupling of N-hydroxyphthalimide esters and bromoalkynes is presented. This reductive cross-electrophile coupling is the first to use aC (sp)ÀXe lectrophile,a nd appears to proceed via an alkynylnickel intermediate.T he internal alkyne products are obtained in yields of 41-95 %w ithout the need for ap hotocatalyst, light, or as trong oxidant. The reaction displays abroad scope of carboxylicacid and alkyne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Based on our investigations and related studies, 14,60,64 a tentative mechanism is proposed in Fig. 5.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Based on our investigations and related studies, 14,60,64 a tentative mechanism is proposed in Fig. 5.…”
Section: Resultsmentioning
confidence: 69%
“…Addition of TMSCl (known to activate the Mn(0) surface 66 ) to the reaction system was somewhat detrimental (Table 1, entry 7), whereas ZnCl2 or MgBr2 additives 67 also reduced the yield of 4a (Table 1, entries 8 and 9). Considering the previously reported role of lithium salts in minimizing diyne formation, 14 we found that the use of LiBr (0.5 equiv.) indeed improved results, affording 4a in 76% yield (73% isolated; Table 1, entry 10).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As shown in Scheme 7b, the appropriate combination of catalytic reductive dialkylation of unsaturated amides and catalytic decarboxylative cross-coupling can enable multiple carbon-carbon linkages to be installed in a regioselective fashion, thus providing an expedient avenue to create complexity and diversity for compound library synthesis. To further illustrate this versatility, N-(acyloxy)phthalimides derived from dialkylation adducts were subjected to established decarboxylative transformations 13c, 17,18 (furnishing C(sp)C(sp 3 ), C(sp 2 )C(sp 3 ) and C(sp 3 )C(sp 3 ) bonds) to give 15ac in 8186 % yield (Scheme 7b).…”
Section: Scheme 7 Access To Medicinally Relevant Molecules and Further Transformations Amentioning
confidence: 99%